Second-line rescue treatment of Helicobacter pylori infection: Where are we now? - Lin, Te-Fu (World J Gastroenterol, 2018)
At present, the best rescue therapy for Helicobacter pylori (H. pylori) infection following failure of first-line eradication remains unclear. The Maastricht V/Florence Consensus Report recommends bismuth quadruple therapy, or fluoroquinolone-amoxicillin triple/quadruple therapy as the second-line therapy for H. pylori infection. Meta-analyses have shown that bismuth quadruple therapy and levofloxacin-amoxicillin triple therapy have comparable eradication rates, while the former has more adverse effects than the latter. There are no significant differences between the eradication rates of levofloxacin-amoxicillin triple and quadruple therapies. However, the eradication rates of both levofloxacin-containing treatments are suboptimal. An important caveat of levofloxacin-amoxicillin triple or quadruple therapy is poor eradication efficacy in the presence of fluoroquinolone resistance. High-dose dual therapy is an emerging second-line therapy and has an eradication efficacy comparable with levofloxacin-amoxicillin triple therapy. Recently, a 10-d tetracycline-levofloxacin (TL) quadruple therapy comprised of a proton pump inhibitor, bismuth, tetracycline and levofloxacin has been developed, which achieves a markedly higher eradication rate compared with levofloxacin-amoxicillin triple therapy (98% vs 69%) in patients with failure of standard triple, bismuth quadruple or non-bismuth quadruple therapy. The present article reviews current second-line anti-H. pylori regimens and treatment algorisms. In conclusion, bismuth quadruple therapy, levofloxacin-amoxicillin triple/quadruple therapy, high-dose dual therapy and TL quadruple therapy can be used as second-line treatment for H. pylori infection. Current evidence suggests that 10-d TL quadruple therapy is a simple and effective regimen, and has the potential to become a universal rescue treatment following eradication failure by all first-line eradication regimens for H. pylori infection.